Peningkatan Kinerja Keuangan Melalui Implementasi Corporate Social Responsibility, Corporate Governance dan Struktur Modal - Kesya Adinda Sukarno; Zulfikar (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR), board of directors, board of commissioners, audit committee, and capital structure on the financial performance of Consumer Non-Cyclicals companies on the Indonesia Stock Exchange for the 2021–2023 period. Using a quantitative approach and purposive sampling, a sample of 27 companies with 79 observations data was obtained after outlier elimination. Data analysis using multiple linear regression with SPSS. The results partially show that CSR, the board of directors, and the board of commissioners have no significant effect on financial performance. Conversely, the audit committee and capital structure have a negative and significant effect. Simultaneously, all independent variables significant affect financial performance with an Adjusted R Square of 0.345 (34.5%), while the rest is influenced by other factors outside the model. These findings emphasize the importance of effective corporate governance and proper capital structure management in maintaining company’s financial stability.